Traitors or patriots? : a story of the German anti-nazi resistance - Eltscher, Louis R. (McNidder & Grace, 2020)
Zusammenfassung: This book is essential reading for anyone with an interest in the anti-Nazi resistance. Little is known today of the extent and intensity of the anti-Nazi activity that occurred inside Hitler's Germany. Even less is known about those whose courage and conviction drove them to risk-and lose-everything to bring the Third Reich to an end. Presented within the broader context of German history and contemporary world events, this comprehensive study relies on extensive historiography by noted scholars to produce a well-balanced, timely narrative of the German resistance to one of history's most violent regimes. Traitors or Patriots? tells a story of incredible courage and conviction that transcends time and place-a story for our own time and for all time. Drawing on extensive sources, author Louis R. Eltscher examines the role of the German anti-Nazi resistance inside the Third Reich in Traitors or Patriots? Beginning with the post-World War I German society that led to Hitler's role as fuhrer, Eltscher documents the rise of anti-Nazi activity, different types of resistance groups, and the difficulties in achieving organization. In addition, Eltscher discusses the role of the German Army in detail. He reveals how the resistance determined that Hitler's elimination by the German Army remained the key to success. Eltscher profiles key resistance figures, considers the reality of an omnipresent totalitarian police state, and studies the moral issues the resistors faced.